APPLICATION OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN THE MEDICAL AND HEALTHCARE SECTOR - SINGH, NARDEV (International Journal of Psychosocial Rehabilitation, 2021)
In this paper, we are going to discuss how the operations of Artificial Intelligence are boosting and involvement of machine learning is being increased from the last few years. Through this research we will also mention how different medical and healthcare organisation of different sizes, types and of various specialities are being more interested through its implementation. This context is also going to let us understand how such systems will become more advanced and thus, attain a huge potential and capability to carry out a wide range of tasks without the human control or input. Although, we will also come to understand that their applications can perform such tasks in a more improved manner apart from humans, but its execution at an extensive scale in similar sectors will also prevent huge number in computerization of healthcare skill full jobs for a hefty period. Such technologies will be helpful in rural and inaccessible areas where there is inadequacy of human resources. But, towards its complete adoption it is significantly substantial to train personnel’s in AI and machine learning so that they are able to carefully supervise as well as manage sensitive healthcare information protect data against theft to consider its use effectively.